Factors Influencing User Adoption Of E-Payment: A Study Of Linkaja In Institut Teknologi Telkom Purwokerto - Mundita Assandy, Agil; Ganis Sukoharsono, Eko (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2025)
The increasing use of e-payment systems emphasizes the need to understand the factors that drive user adoption, as these systems provide efficient and convenient financial transactions. This study explores the determinants influencing the adoption of LinkAja at Institut Teknologi Telkom Purwokerto (ITTP) in 2023, utilizing the Technology Acceptance Model (TAM). Key constructs analyzed include perceived usefulness, ease of use, trust, risk, attitude, and behavioural intention. The study involved a population from ITTP, with a sample of 100 participants selected through convenience sampling. A quantitative approach was employed, collecting data via structured questionnaires and analyzing it using Partial Least Squares (PLS) modelling. The findings indicate that perceived usefulness, ease of use, and trust positively and significantly influence attitudes, which in turn affect the behavioural intention to adopt e-payment systems. On the other hand, perceived risk did not significantly impact user attitudes, likely due to increasing trust in digital platforms. These results highlight the need to design e-payment systems that are user-friendly, transparent, and trustworthy. Providers are advised to focus on enhancing utility, ease of understanding, and reliability to foster positive user attitudes and encourage adoption.